2010
DOI: 10.1021/jp911922a
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Cage Tungsten Oxide Clusters in the Gas Phase

Abstract: During the course of a study on the clustering of W-Se and W-S mixtures in the gas phase using laser desorption ionization (LDI) , stand out as intense peaks in the regular mass spectral pattern of tungsten oxide clusters suggesting unusual stabilities for them. Moreover, these clusters do not fragment in the postsource decay analysis. While trying to understand the precursor material, which produced these clusters, we found the presence of nanoscale forms of tungsten oxide. The structure and thermodynamic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…25 Also, the B3LYP functional and LANL2DZ basis set have been previously used for studying transition metal oxide clusters. [35][36][37][38][39] Not every configuration of each MC step was optimized. After running the MC simulation, we obtained local minimum energy structures among all of the configurations.…”
Section: Methodsmentioning
confidence: 99%
“…25 Also, the B3LYP functional and LANL2DZ basis set have been previously used for studying transition metal oxide clusters. [35][36][37][38][39] Not every configuration of each MC step was optimized. After running the MC simulation, we obtained local minimum energy structures among all of the configurations.…”
Section: Methodsmentioning
confidence: 99%
“…Although there are well known deficiencies with the B3LYP functional (particularly for excited states63), there are plenty of studies of transition metal clusters (neutral and charged) for which the B3LYP/LANL2DZ basis set has been used successfully 6468. For TiO 2 and TiO, Qu and Kroes64 found (in comparison to experiment) vibrational frequencies accurate to about 60 wavenumbers, ionization energies accurate to 0.2 eV, and electron affinities accurate to 0.2 eV.…”
Section: Methodsmentioning
confidence: 99%
“…26,27 This suggests that MB could be a good candidate as a catalyst in some challenging selective oxidation reactions. For this reason we have explored whether or not the Mo V -O-Mo VI bridging structure in MB is active for selective redox chemistry 6,[8][9][10][11][12][13] by testing it for the oxy-functionalization of cyclohexane.…”
Section: Cyclohexane Oxidation Using Mb As a Catalystmentioning
confidence: 99%
“…9 There has been particular interest in utilising molybdenum oxide containing catalysts, including the use of heteropolyacids. 10,11,12 In the majority of these reports the molybdenum is usually present as Mo VI species. However, it has been demonstrated that an activating pre-treatment step in an H 2 or a hydrocarbon atmosphere is very important in establishing the activity and selectivity of oxidized molybdenum carbides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation